Effective contribution ratio of the molar during sequential distalization using clear aligners and micro-implant anchorage: a finite element study - Xulin Liu; Junjie Wu; Yuxun Cheng; Jie Gao; Yi Wen; Yubohan Zhang; Houzhuo Luo; Zuolin Jin; Yanning Ma (SpringerOpen, 2023)
Abstract Introduction This study aims to investigate the biomechanical effects of anchorage reinforcement using clear aligners (CAs) with microimplants during molar distalization. And also explores potential clinical strategies for enhancing anchorage in the sequential distalization process. Methods Finite element models were established to simulate the CAs, microimplants, upper dentition, periodontal ligament (PDL), and alveolar bone. In group set I, the 2nd molars underwent a distal movement of 0.25 mm in group set II, the 1st molars were distalized by 0.25 mm after the 2nd molars had been placed to a target position. Each group set consisted of three models: Model A served as the control model, Model B simulated the use of microimplants attached to the aligner through precision cuts, and Model C simulated the use of microimplants attached by buttons. Models B and C were subjected to a series of traction forces. We analyzed the effective contribution ratios of molar distalization, PDL hydrostatic stress, and von Mises stress of alveolar bone. Results The distalization of the 2nd molars accounted for a mere 52.86% of the 0.25-mm step distance without any reinforcement of anchorage. The remaining percentage was attributed to the mesial movement of anchorage teeth and other undesired movements. Models B and C exhibited an increased effective contribution ratio of molar distalization and a decreased loss of anchorage. However, there was a slight increase in the undesired movement of molar tipping and rotation. In group set II, the 2nd molar displayed a phenomenon of mesial relapse due to the reciprocal force produced by the 1st molar distalization. Moreover, the efficacy of molar distalization in terms of contribution ratio was found to be positively correlated with the magnitude of force applied. In cases where stronger anchorage reinforcement is required, precision cuts is the superior method. Conclusions The utilization of microimplants in conjunction with CAs can facilitate the effective contribution ratio of molar distalization. However, it is important to note that complete elimination of anchorage loss is not achievable. To mitigate undesired movement, careful planning of anchorage preparation and overcorrection is recommended.